2015
DOI: 10.1186/s12889-015-1396-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of social networking platforms for sexual health promotion: identifying key strategies for successful user engagement

Abstract: BackgroundOnline social networking platforms such as Facebook and Twitter have grown rapidly in popularity, with opportunities for interaction enhancing their health promotion potential. Such platforms are being used for sexual health promotion but with varying success in reaching and engaging users. We aimed to identify Facebook and Twitter profiles that were able to engage large numbers of users, and to identify strategies used to successfully attract and engage users in sexual health promotion on these plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 29 publications
(39 reference statements)
6
79
0
3
Order By: Relevance
“…Results for study aim 1 indicate that social media appears to be a useful tool for engaging Latino immigrant youth in health promotion programming. These levels of reach and engagement are on par with those seen in other studies examining health promotion efforts using social media [58][59][60][61]. Despite the existence of numerous barriers to participation in traditional in-person programming, we were able to achieve a reasonable level of engagement through the Adelante Facebook page.…”
Section: Principal Findingssupporting
confidence: 67%
See 1 more Smart Citation
“…Results for study aim 1 indicate that social media appears to be a useful tool for engaging Latino immigrant youth in health promotion programming. These levels of reach and engagement are on par with those seen in other studies examining health promotion efforts using social media [58][59][60][61]. Despite the existence of numerous barriers to participation in traditional in-person programming, we were able to achieve a reasonable level of engagement through the Adelante Facebook page.…”
Section: Principal Findingssupporting
confidence: 67%
“…Past research has identified some strategies for successful user engagement, including high sustained levels of social media activity [58] and targeted social media campaigns [59], among others. Results from study aims 2 and 3 highlighted that posting during the targeted social media outreach campaign period and boosting posts both resulted in higher user engagement.…”
Section: Principal Findingsmentioning
confidence: 99%
“…These profiles addressed the relation of HPV with cervical cancer, general information, importance of check-ups and cervical smear/Papanicolaou test, the prevalence of the virus in men and prevention. Both profiles contained the same number and types of publications (videos, images, links to specialised sources and informative posters) following the recommendations of previous research on social networks and mediation, which recommend the use of multimedia, links to specialised sources, short publications, and frequent interventions to make attractive a Facebook profile about health matters (Zang, Tsark, Campo and Teti, 2015;Syred, Naidoo, Woodhall and Baraitser, 2014;Veale, Sacks-Davis, Weaver, Pedrana, Stoové and Hellard, 2015). In the narrative profile, the information was presented through the story of a real subject, a girl diagnosed with HPV who, while waiting for the results to know whether the infection is high or low risk, tells its own story and gives information on the profile through posts and videos.…”
Section: Methodsmentioning
confidence: 99%
“…Asimismo, varios de estos estudios se centran en un área más concreta, como la dermatología (GarcíaRo mero, Prado, DominguezCherit, HojyoTomomka & Arenas, 2011); la urología (Sajadi & Goldman, 2011); la diabetes (Greene, Choudhry, Kilabuk & Shrank, 2011;Hunt, 2015), las enfermedades raras (Armayones et al 2015); el estrés y la depresión (Egan & Moreno, 2011a), la educación sexual (Veale et al, 2015); o el consumo de alcohol (Egan & Moreno, 2011b;Lyons, Goodwin, McCreanor & Griffin, 2015;Moreno & Whitehill, 2014), de tabaco (Jacobs, Cobb, Abroms & Graham, 2014), de opio (Lord, Brevard & Budman, 2011); la donación de órganos (Peña, 2013), el sida (Menacho, Galea & Young, 2015) o el sector farmacéutico (Kukreja, Sheehan & Riggins, 2011).…”
Section: Marco Teóricounclassified